SC1 Paediatric In-situ simulation: a method of building multiprofessional experience and teamwork. (3rd November 2019) - Patel, Ashish; Holt, Ashley; Copeman, Annabel
Abstract : Background: Alarmingly, nearly 30% of paediatric inpatients can be harmed during their hospital stay. Recently, the demand for paediatric services has increased. Combine this with reduced training hours for trainees, less exposure to patients and rotating hospitals every 6 months, it can be challenging to develop relationships within teams before emergency situations arise. Simulation-based education provides a useful tool to support learning within paediatrics. In-situ simulation teaching is a low cost, using the regular team in their own environment with their normal set up and equipment. By establishing an in-situ paediatric simulation programme, we aimed to promote team learning but also enable these multidisciplinary relationships to form early. Summary of programme: We delivered a low fidelity fortnightly ward-based simulation within our department replicating common scenarios that the team may face in real life. Scenarios are based on the Royal College of Paediatric and Child Health (RCPCH) Progress curriculum. Beforehand the team receives a brief, with debrief following the scenario to facilitate learning. All staff acted as their current role and includes any members of the paediatric ward team including doctors, nurses, healthcare assistants, medical/nursing students, and consultants. Feedback is obtained using a combination of free text questions and Likert scales. Summary of results: The feedback has been extremely positive with the whole team finding the in-situ training worthwhile for their learning. We have delivered 16 in-situ simulations so far to 153 participants. 85% of candidates have reported an improvement in their confidence following the scenario with average confidence increasing from 2.57 to 3.68/5 post teaching. 54% of candidates comment never seeing the scenario in real life before the session. Feedback comments have shown an improvement in the team's knowledge and management of paediatric problems. It has facilitated quicker integration of trainees into our department, with better communication and working relationships with the ward staff as well as an understanding of each other's roles. Organisational and equipment have also been highlighted and acted upon. Discussion, conclusions, recommendations: In-situ simulation has been a hugely beneficial training method for our staff to gain confidence in a wide variety of acute paediatric situations. Interprofessional working and education is also promoted. Latent safety threats may be elicited and changed, improving patient safety. By maintaining our in-situ simulation programme we hope to continue enhancing interprofessional learning and training within our department. In situsimulation can be easily setup by other teams to obtain similar rewards References: Sharek PJ, Classen D. The incidence of adverse events and medical error in paediatrics. Pediatr Clin north Am 2006;53: 1067–77 Cleriher L, Rowney D, Ker J. Simulation in paediatric training. BMJ Arch Dis Child Educ Pract Ed 2016; 101: 8–14